2016
DOI: 10.1111/ajt.13773
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Pregnancy After Kidney Transplantation and Risk of Allograft Failure

Abstract: The optimal timing of pregnancy after kidney transplantation remains uncertain. We determined the risk of allograft failure among women who became pregnant within the first 3 posttransplant years. Among 21 814 women aged 15-45 years who received a first kidney-only transplant between 1990 and 2010 captured in the United States Renal Data System, n = 729 pregnancies were identified using Medicare claims. The probability of allograft failure from any cause including death (ACGL) at 1, 3, and 5 years after pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 26 publications
1
43
1
4
Order By: Relevance
“…28 A recent analysis of US Medicare data described elevated rates of graft loss with conception up to 24 months after KT. 29 Pre-existing hypertension and severity of graft dysfunction prior to conception have been shown to be independently associated with graft failure in KT recipients. [30][31][32] it is uncertain whether there is disproportionate reduction in bound versus free tacrolimus levels.…”
Section: Maternal/graft Risksmentioning
confidence: 99%
“…28 A recent analysis of US Medicare data described elevated rates of graft loss with conception up to 24 months after KT. 29 Pre-existing hypertension and severity of graft dysfunction prior to conception have been shown to be independently associated with graft failure in KT recipients. [30][31][32] it is uncertain whether there is disproportionate reduction in bound versus free tacrolimus levels.…”
Section: Maternal/graft Risksmentioning
confidence: 99%
“…Waiting longer may also result in impaired renal function postpartum which may fail to recover with already declining renal function due to chronic allograft nephropathy. However, a recent study reported that there is an increased risk of allograft failure to pregnancies in both first posttransplant year (HR: 1.25; 95% CI: 1.04, 1.50) and second posttransplant year (HR: 1.26; 95% CI: 1.06, 1.50), while pregnancy in the third posttransplant year was not associated with an increased risk of death censored graft loss [30]. …”
Section: Optimal Time To Conceptionmentioning
confidence: 99%
“…It has therefore been a focus on pregnancy safety and outcome for immunosuppressed women. 3-5 Mycophenolic acid (MPA) is the active immunosuppressive substance in both mycophenolate mofetil (MMF) and mycophenolate sodium (MPS), and it reduces the incidence of acute rejection and benefits graft survival. 6 From previous studies, it is well known that exposure to MPA in early pregnancy of female transplant recipients has been associated with increased rate of miscarriages and birth defects in the live born.…”
mentioning
confidence: 99%